Leveraging IT to Improve Patient Safety - Ball, M.J.; Garets, D.E.; Handler, T.J. (Yearbook of Medical Informatics, 2003)
Medical errors and issues of patient safety are hardly new phenomena. Even during the dawn of medicine, Hippocrates counselled new physicians “to above all else do no harm.” In the United States, efforts to improve the quality of healthcare can be seen in almost every decade of the last century. In the early 1900s, Dr. Ernest Codman failed in his efforts to get fellow surgeons to look at the outcomes of their cases. In the 1970s, there was an outcry that the military allowed an almost blind surgeon to continue to practice and even transferred him to the prestigious Walter Reed Hospital. More recently, two reports by the Institute of Medicine caught the attention of the media, the American public, and the healthcare industry. To Err Is Human highlights the need to reduce medical errors and improve patient safety, and Crossing The Quality Chasm calls for a new health system to provide quality care for the 21st century.